The Good News and the Bad News. - Wolf, Wayne (Computer (00189162), 2007)
The article discusses the challenges of designing embedded computing systems. Embedded systems function in real-time, but current theory underlying real-time computing is incomplete. The control of big, physically distributed system using embedded technology likewise demands further study. Aligning power needs with power availability offers yet additional challenges. One way to increase the speed of embedded systems is to hard-wire functionality onto a chip rather than use software. Multiprocessors let one relegate distinct, real-time tasks to separate processing units.